2012
DOI: 10.7498/aps.61.062802
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of solid-deuterium induced by infrared irradation

Abstract: In this paper, the internal mechanism of solid deuterium spatial distribution induced by infrared radiation is studied. The changes in spatial distribution and micro-structure of solid deuterium are also discussed as the results of wavelength and heating time of IR light. It is found that the micro-structure of solid deuterium which is irradiated by a special IR light is changed from polycrystal to monocrystal, the solid deuterium is redistributed and becomes more uniform and transparent. The best wavelength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…where I 0 is the incident IR light power at x = 0, V is the volume at the position x, and α is the absorption coefficient of the material. In our experiment, the absorption coefficients [12] of solid D 2 and quartz are 1.02 cm −1 and 1.55 cm −1 , respectively. Some intrinsic parameters [14] of solid D 2 and quartz are shown in Table 1.…”
Section: Analysis and Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…where I 0 is the incident IR light power at x = 0, V is the volume at the position x, and α is the absorption coefficient of the material. In our experiment, the absorption coefficients [12] of solid D 2 and quartz are 1.02 cm −1 and 1.55 cm −1 , respectively. Some intrinsic parameters [14] of solid D 2 and quartz are shown in Table 1.…”
Section: Analysis and Discussionmentioning
confidence: 48%
“…In our previous studies, [12] a strong absorption peak was found at 3140 nm by measuring the IR absorption spectra of liquid D 2 at different temperatures. In the present experiment, the incident IR light is selected to be 3140 nm in wavelength and 100 µW in power.…”
Section: Resultsmentioning
confidence: 91%